2017
DOI: 10.1097/wnr.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Expression of brain-derived neurotrophic factors, neurotrophin-3, and neurotrophin-4 in the nucleus accumbens during heroin dependency and withdrawal

Abstract: Neurotrophins, brain-derived neurotrophic factors (BDNF), neurotrophin-3 (NT-3), and neurotrophin-4 (NT-4), have been implicated in the modulation of heroin dependency. This study was designed to explore the expression alterations of BDNF, NT-3, and NT-4 in the context of heroin dependence and withdrawal in the rat nucleus accumbens (NAc). Heroin dependence was induced by a progressive intraperitoneal treatment of heroin. The results showed that the expression levels of BDNF and NT-4 were significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In our study, the weight of rats in the HA and HR groups was lower than that of rats in the control group. These results are in agreement with previous observation (Li, Xia, Li, Yin, Wang, et al 2017) and were probably caused by heroin-mediated activation of mu-opioid receptors in the intestinal wall and inhibition of pathways in the enteric nervous system, resulting in reduced peristalsis and slowed intestinal transit (Leppert 2015). Moreover, the weight loss of rats in the HR group was more pronounced, which may have been because long-term continuous addiction leads to more serious gastrointestinal damage.…”
Section: Behavior and Weight Losssupporting
confidence: 92%
“…In our study, the weight of rats in the HA and HR groups was lower than that of rats in the control group. These results are in agreement with previous observation (Li, Xia, Li, Yin, Wang, et al 2017) and were probably caused by heroin-mediated activation of mu-opioid receptors in the intestinal wall and inhibition of pathways in the enteric nervous system, resulting in reduced peristalsis and slowed intestinal transit (Leppert 2015). Moreover, the weight loss of rats in the HR group was more pronounced, which may have been because long-term continuous addiction leads to more serious gastrointestinal damage.…”
Section: Behavior and Weight Losssupporting
confidence: 92%
“… 30 The expression levels of BDNF in the NAc of rats significantly decrease after chronic heroin treatment, whereas BDNF expression is significantly increased in these rats when they undergo either naloxone‐induced withdrawal or spontaneous withdrawal 1 day after the last heroin treatment. 31 However, this explanation is in conflict with that of another study that suggests that BDNF protein in the NAc is not involved in heroin incubation. 21 Several methodological issues should be considered when these discrepant results are interpreted.…”
Section: Discussionmentioning
confidence: 88%
“…To further explore the underlying mechanism, the community succession of the gut microbiome was detected after various treatments via 16S rRNA sequencing. The findings revealed that His treatment increased the relative abundance of Proteobacteria, indicating the occurrence of dysbiosis (Li et al, 2017). At the genus level, His treatment promoted Lachnospirace-ae_NK4A136_group and norank_f_Lachnospiracae relative abundance, which was reported to be increased by Fubrick tea attenuates (Shin et al, 2015).…”
Section: Discussionmentioning
confidence: 86%